Effective PRCs positioning for PAPR reduction using PRCs in OFDM systems - Yew, Sin Giap; Tan, Chong Eng (IEEE, 2009)
In this paper, the effective use of peak reduction carrier (PRC) for PAPR reduction is evaluated. By taking into account the number of PRCs, its position and PRC-to-Data ratio, the recommendation on how to effectively adopt PRC for PAPR reduction is carried out for OFDM systems with sub-carriers from 64 sub-carriers to 8192 sub-carriers. From our simulations, it has been shown that there are effective positions for PRC allocation as well as a balance needs to be strike for transmission efficiency versus PAPR reduction effectiveness evaluated via the PRC-to-Data ratio.